Introduction to the thematic file: Knowledge Sharing in Geographically Dispersed Communities - Goglio-Primard, Karine; Guittard, Claude; Burger-Helmchen, Thierry (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
This chapter aims at a better understanding of the dynamics leading firms to create Networks of practice (NoP) to transfer knowledge and know-how between its geographically dispersed business units. In this introduction we focus on the complementarity between communities of practice (CoP) and networks of practice (NoP) inside firms to share knowledge and consolidate organizational learning. We show that informal settings where people interact around their practices, such as CoP facilitate and consolidate knowledge sharing inside firms and enable them to create a larger network. After a literature review on CoP and NoP, the chapter will highlight the role of CoP and boundaries processes (brokers, boundary objects) in the development of NoP.